Mangrove Conditions Using Drones Along Several Rivers in Bengkalis Island, Riau, Indonesia - Eki Ria Saputra; Sri Catur Setyawatiningsih; Radith Mahatma; Kozan, Osamu (Biosaintifika: Journal of Biology & Biology Education, 2024)
Mangroves on Bengkalis Island experienced a decline between 2000 and 2019. This decrease in mangrove forest area was caused by anthropogenic activities and natural factors, such as coastal erosion. The objective of this study is to assess the current condition of mangroves on Bengkalis Island, Riau, Indonesia. The research was conducted in March 2024 across four rivers on Bengkalis Island, with each river containing three research stations: upstream, midstream, and downstream. Data collection involved capturing aerial photos of mangroves using drones over 100 m x 100 m. The photos were analyzed using the supervised image classification method to identify and assess mangrove land cover. A total of 11 mangrove species were identified along the rivers. The most widely distributed species across all locations were Rhizophora apiculata and Xylocarpus granatum. Canopy cover at all research sites was classified as dense, with coverage exceeding 75%. This study provides crucial information about the condition of mangroves on Bengkalis Island, serving as a guideline for future restoration efforts.